Penerapan Algoritma TextRank dan Dice Similarity Untuk Verifikasi Berita Hoax - Christian Khontoro; Justinus Andjarwirawan; Yulia Yulia (Jurnal Infra, 2021)
Hoax or in Indonesian, hoax is fake news or news that has no source. Hoax are a series of information that is misguided, but sold as truth[5]. The problems above are the basis for creating a verification system for this hoax news. The TextRank and Dice Similarity algorithms will be used to help verify the inputed news is a hoax or fact. Where in this study, the TextRank algorithm is used to find the most important keywords in a news which will then be used to become keywords in search engines. Then the Dice Similarity algorithm is used to measure the level of similarity of the news entered with the news obtained from search results on search engines. The hoax verification system that has been done has been tested using several similarity weights to find which similarity weights are the most optimal. The data used were 50 hoax news and 50 fact news. From this test, the optimal similarity weight is 40% with an accuracy of 84%. With details of 50 hoax data, 47 news were declared hoax, 2 news items were declared facts, and 1 news was declared unknown. Of the 50 fact news, 37 news were declared facts, 13 were declared hoax, and no news was declared unknown.